Can Health Foreign Assistance Break the Medical Brain Drain? - Yasser Moullan (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2009)
This paper analyses the impact of health foreign assistance on physicians' brain drain. We use the database from Bhargava and Docquier (2008) to explain physicians' brain drain and health foreign assistance from 1995 to 2003 using a bilateral gravity equation model. In the first time, we propose to investigate the direct and reverse impact of health assistance through Simultaneous Equation Model with Three-Stage Least Squares (3SLS) methodology and highlight a significant negative effect of health foreign assistance on the medical brain drain whereas emigration rate of doctor increases the amount of health aid received by recipient countries. In a second time, we analyzed the indirect effect of health aid via epidemics prevalence through the death rate per 1000 people. We find that health aid plays a key role in the improvement of vaccination, treatment and prevention which may reduce death rate and, finally, decreases the physicians emigration rates. These findings confirm the efficiency of health foreign aid to weaken the vicious circle of physicians drain.
Keywords: F22; F35; O15; C23; I1; O11; 330; International Migration; Physicians Emigration Rates; Foreign Aid; Health foreign assistance; Simultaneous Equation Model; Three Stage Least Squares; Gravity Equation model